As chuvas no município de João Pessoa: impactos, riscos e vulnerabilidade socioambiental - Silva, Natieli Tenório da (2018)
The objective of this research is to study the relation between the varying degrees of socioenvironmental vulnerability and the events of rainfall impacts in the municipality of João Pessoa-Paraíba. To this purpose, the work was based on the geographic approach to climate developed respectively, by Monteiro (1976) and Sant'Anna Neto (2001, 2008, 2011). In addition, Alves (2006, 2007, 2013) was used as a methodological reference, through which the areas of environmental risk and social risk were identified, by census sector, thus enabling overlapping, and obtaining the socioenvironmental vulnerability rate of the municipality, whose variation is ranked as the following: very low, low, medium, high and very high. Furthermore, the impacts and damages caused by the rains, to which the population was affected, were raised for the period 1983 to 2016 through a survey in the information base of “A União” journal; subsequently, a proposal was made to classify the extreme rainfall thresholds that trigger damage, through the processional dynamics of the rain-damage binomial. It was verified that the flat condition of the relief presented in the study area conditions the happening of a greater risk of floods and inundations, than to landslides, since the municipality was impacted mainly by the happening of floods, accounting for 67.02% of the total impacts. It was found that the sectors whose social risk falls into the high and very high category occupy 40.61% of the municipality, concentrating predominantly in the south and west zones. Regarding socioenvironmental vulnerability, it was found that the municipality presents 54.94% of its territorial area in the condition of high and very high vulnerability, which is concentrated specially in the south and west zones. It was observed that the total number of homeless people arises as the human damage that presented the highest percentage, reaching 99.17%; and that the period of highest incidence corresponds to 1983-1989 with 51.75% of the total human damages. As for material damages, the type of destruction damage accounted for 67.19% of the total, in the period 2000-2010, registering 38.60% of total incidences. Finally, this work constitutes a necessary instrument for the accomplishment of future interventions in geographical space, by the municipal agencies, in order to mitigate and /or solve the socioenvironmental problems to which the population is exposed because of rainfall.